Characterization of blaCTX-M-14 transposition from plasmid to chromosome in Escherichia coli experimental strain - Kouta Hamamoto; Toshiro Tokunaga; Nobuyoshi Yagi; Itaru Hirai (Elsevier, 2020)
Mostly, blaCTX-M is found on transferable plasmids as a component of the blaCTX-M transposition unit containing an insertion sequence, ISEcp1, which exists on the upstream region of blaCTX-Ms. Several recent studies conducted in clinical and community settings have reported the presence of chromosomally located blaCTX-M in extended spectrum β-lactamase (ESBL)-producing bacterial isolates. In this study, we observed the frequency and molecular nature of the ISEcp1-mediated transposition of blaCTX-M-14 from a plasmid to a chromosome by using an experimental strain of Escherichia coli. We determined 102 different chromosomal transposition sites of blaCTX-M-14 in 126 E. coli isolates following five independent screening procedures. The characterization of the 102 different chromosomal transposition sites of blaCTX-M-14 observed in this study revealed the presence of 5-bp direct repeat (DR) sequences and identical left terminal inverted sequences in 80 E. coli isolates. However, 5'-flanking sequences of the right terminal DR sequences in the 80 E. coli isolates were highly diverse, and consensus sequences of the right terminal inverted repeat sequences were not observed. In case of our E. coli experimental strain, the frequency of the ISEcp1-mediated transposition of blaCTX-M-14 from a plasmid to a chromosome was determined to be 0.51% (SD = 0.37). Collectively, the molecular nature of ISEcp1 could plausibly be a factor contributing to the high detection rates of E. coli possessing chromosomally located blaCTX-M-14 in both clinical and community settings.